2014
DOI: 10.1136/heartjnl-2014-305873
|View full text |Cite
|
Sign up to set email alerts
|

Two decades of experience with the Ross operation in neonates, infants and children from the Italian Paediatric Ross Registry

Abstract: Despite low hospital risk and satisfactory late survival, paediatric Ross operation bears substantial valve-related morbidity in the first two decades. Contrary to expectation, autograft reoperation is more common than homograft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
35
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 27 publications
(73 reference statements)
4
35
0
3
Order By: Relevance
“…Focusing on PC, aortic homografts were employed in the 1960s, followed by porcine xenografts in Dacron fabric tubes in the 1970s. The secondary finding of the study is that freedom from reoperation is significantly lower than that observed in age-matched children having orthotopic HG (7), although in line with results by Tweddell (54% at 10 years) and Brown (43% at 15 years). Between the late 1980s and the 1990s, novel design xenograft conduits became available for clinical use, although late outcomes reported for these conduits were disappointing (8,9).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Focusing on PC, aortic homografts were employed in the 1960s, followed by porcine xenografts in Dacron fabric tubes in the 1970s. The secondary finding of the study is that freedom from reoperation is significantly lower than that observed in age-matched children having orthotopic HG (7), although in line with results by Tweddell (54% at 10 years) and Brown (43% at 15 years). Between the late 1980s and the 1990s, novel design xenograft conduits became available for clinical use, although late outcomes reported for these conduits were disappointing (8,9).…”
Section: Discussionsupporting
confidence: 84%
“…Indications for replacement of the original PC were conduit stenosis with a gradient greater than 40 mm Hg, RV pressures 75% or more of left ventricular pressure or echocardiographic and MRI evidence of progressive RV dilation or tricuspid valve regurgitation, or both, associated with right heart failure due to PC dysfunction. In order to define outcome of heterotopic PC implantation in infants and children treated at our institution, comparison with data in 305 children and with a median age of 9.4 years, receiving orthotopic PC, either HG (n = 281) or XG (n = 24) between 1990 and 2012 (Italian Pediatric Ross Registry) was undertaken (7).…”
Section: Study Population and Operative Datamentioning
confidence: 99%
“…Overall 15-year freedom from any left ventricular outflow tract reintervention was 59%; 85% still had their autograft valve at the latest follow-up. Left ventricular outflow tract reintervention was uncommon in infants (n [ 2). Overall 15-year freedom from right ventricular outflow tract reintervention was 53%, and was lower in infants (19%) than in children (51%) and adolescents (76%; p < 0.0001).…”
mentioning
confidence: 81%
“…Children and adolescents have higher rates of left ventricular outflow tract reintervention, whereas infants are at highest risk of right ventricular outflow tract reintervention. T he Ross procedure is commonly used in children requiring aortic valve replacement [1,2]. Advantages include autograft growth potential, excellent flow characteristics, and avoidance of anticoagulation [3,4].…”
mentioning
confidence: 99%
“…To the Editor, We have read the interesting article from Luciani and colleagues1 documenting the outcomes into the second decade after the Ross procedure in infants and children from the Italian Paediatric Ross Registry. The conclusion concisely stated that the Ross procedure was a low-risk palliative procedure for aortic valve abnormalities at the expense of valve-related reoperation.…”
mentioning
confidence: 99%